Needs, effectiveness and limitations of the industrial policy of Serbia - Leković, Vlastimir; Mićić, Vladimir (Industrija, 2013)
Based on the position and the role of the industry that decisively affects the overall level of economic dynamics (GDP growth, employment rate, exports, competitiveness, innovation) this paper discusses some of the key factors which in an environment of deindustrialization of the Serbian economy call for the development and implementation of industrial policy, which is, again, the essential requirement for reindustrialization of the country. Building on the theoretical and methodological analysis of the most dominant contemporary concepts of industrial policy, the authors point to the need for setting and implementing an active, flexible and sophisticated industrial policy as an integral part of the socio-economic development of the country, since in this way the accumulation of structural disproportions can be achieved, as well as a more balanced presence on the world market. Current state of the industry characterized by a relatively modest share in the GDP generation and overall employment, low productivity and competitiveness levels, outdated technologies, insufficient innovation and R&D is a result of the irresponsible attitude of the state towards this economic sector. Due to the presence of the existing economic, financial and industrial limitations, it is necessary for the state to define a consistent and sustainable industrial policy concept and include all relevant stakeholders - ministries, employers, trade unions, research institutions and consumer organizations, in its implementation